The effectiveness Village-Owned Enterprises (BUMDes) Sehati in Nekmese Village Amarasi Sub-District, South Kupang Regency - Yopy E. Haekase; Hendrik Toda; Nursalam Nursalam (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: The purpose of this study is to measure and analyze the effectiveness of Sehati Village-Owned Enterprises (BUMDes) in Nekmese Village, South Amarasi District, Kupang Regency. Research Methodology: This study used descriptive research with a qualitative approach that used the effectiveness measurement criteria of Chambell J.P (1989). Results: The findings in this study are that BUMDes has been effective with several successes, namely program success, target success, satisfaction with the program and the achievement of. Limitations: This research only reviewed the effectiveness of BUMDes Sehati in Nekmese village, Kupang Regency. Contribution: This research becomes scientific information for public administration science. Keywords: Effectiveness, BUMDes